Religious Socialization in a High Modern Society - Alexeeva, Ekaterina (KnE Social Sciences, 2021)
This article is devoted to the study of how religious identity and belonging to a religious community becomes a life strategy for socialization, and can help to overcome crises at different stages of life. The text presents an analysis of the autobiographies of those who made religiosity the basis of their way of life and a means of of self-determination. The methodological basis of the research is the combination of the theory of multiple modernities and the method of biographical interviews. Namely, we pay attention to the strategy of constructing religious identity. Sampling was carried out using a combination of reference sampling methods and ‘snowball’, since our previous experience has shown that this combination gives the best results in the study of hard-to-reach religious groups. In total, the sample included 30 respondents at the rate of three representatives of each denomination (Orthodox, Catholics, old believers, Buddhists, Jews) in each of the two cities. They were interviews (in person and on Skype), then the resulting transcripts were processed according to the methodology of the analysis of biographical narrative, described by T. Ingrata. The method of biographical interview removes the problem of psychological barrier in respondents when communicating on sensitive topics, as Hyde does not affect them directly. When planning the sample, we included major denominations represented in Russia — Orthodoxy, Catholicism, Buddhism and Judaism. This procedure allows identifying and describing strategies of behavior, as it is based on the comparison of biographical data of respondents with the ‘told life story’, that is, the consideration of subjective experience in comparison with the real socio-cultural context. Keywords: religious conversion, life crisis, biography, biography method